The importance of prosthetic planning for implant-supported dentures in esthetic zone - Eri Hendra Jubhari; Wilson Pangiawan (Makassar Dental Journal, 2020)
Background: Dental implant is an optional way to replace edentulous area by surgically placing it into soft tissue or jawbone as a root substitute to hold dentures. Placement of the implant, so that the gingival tissue position will restore aesthetics and function properly. Objective: To discuss the importance of prosthetic planning for implant-supported dentures in the aesthetic zone. Case: Sample case of a patient who had previously subjected to dental surgery for implant placement and placement of a crown on tooth 11. The patient reported poor aesthetics due to gingival retraction and changes on the surface of the ceramic material. After proper planning, the prosthesis is reproduced, with the selection of new components and periodontal surgery using modification techniques for handling soft tissue. Nine months postoperatively, patients had better gingival alignment and reported aesthetic and functional satisfaction. Conclusion:Prosthetic planning to implant-supported dentures in the esthetic zone is very important. Several factors have contributed to the success of the treatment, such as implant position, soft tissue morphology, dental aesthetics, and biomechanics of the prosthetic structure. Complications that can occur after implant pla-cement are gingival recession which will primarily interfere with the esthetics of the anterior teeth so that interventional periodontal surgery is required.